THE GROUPING METHOD AS A PEDAGOGICAL STRATEGY TO ENHANCE JUNIOR HIGH SCHOOL STUDENTS' PROFICIENCY IN CONSTRUCTING SIMPLE PRESENT TENSE SENTENCES [METODE PENGELOMPOKKAN SEBAGAI STRATEGI PEDAGOGIS UNTUK MENINGKATKAN KEMAMPUAN SISWA SMP DALAM MENYUSUN KALIMAT SINGKAT DALAM BENTUK PRESENT TENSE] - Edy Suseno; Dian Novita; Fika Megawati (Universitas Pelita Harapan, 2026)
The simple present tense is a fundamental grammar structure in English as a Foreign Language (EFL) learning, yet it remains a source of difficulty for many junior high school students, particularly in relation to subject-verb agreement and sentence construction. This study investigates the effectiveness of the grouping method as a pedagogical strategy to improve students' proficiency in constructing simple present tense sentences. A mixed-methods research design was employed with 60 Grade 7 students from a junior high school in Indonesia. The intervention involved implementing the grouping method in three phases: teaching verbal sentences (Group A: plural/subjects other than third-person singular; Group B: third-person singular), teaching nominal sentences (Group C: to be constructions), and integrating both types of sentences. Data were collected through pre- and post-tests, classroom observations, student questionnaires, and semi-structured interviews. Results indicated a significant improvement in students' accuracy in constructing simple present tense sentences, a reduction in cognitive load, and an increase in motivation and confidence. The findings suggest that the grouping method is a valuable strategy for EFL teachers to enhance students' grammar proficiency and engagement. Abstrak Bahasa Indonesia Simple Present Tense merupakan struktur tata bahasa fundamental dalam pembelajaran Bahasa Inggris sebagai Bahasa Asing (EFL), namun tetap menjadi sumber kesulitan bagi banyak siswa SMP, khususnya terkait dengan kesesuaian subjek-predikat dan konstruksi kalimat. Studi ini menyelidiki efektivitas metode pengelompokan sebagai strategi pedagogis untuk meningkatkan kemampuan siswa dalam menyusun kalimat Simple Present Tense. Desain penelitian metode campuran digunakan dengan 60 siswa kelas 7 dari sebuah SMP di Indonesia. Intervensi melibatkan penerapan metode pengelompokan dalam tiga fase: pengajaran kalimat verbal (Kelompok A: jamak/subjek selain orang ketiga tunggal; Kelompok B: orang ketiga tunggal), pengajaran kalimat nominal (Kelompok C: konstruksi